2012
DOI: 10.1111/j.1745-4514.2011.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Indices, Antioxidant Activity and Anti-Inflammatory Effect of Extracts of the Medicinal Rice “Njavara” and Staple Varieties: A Comparative Study

Abstract: Chemical indices, antioxidant and anti‐inflammatory activity of extracts of bran of medicinal rice – Njavara “black glumed” type (NBb) and its rice (NBr), were studied in comparison with bran and rice of staple varieties: Sujatha and Palakkadan Matta. Total oryzanol, phenolic, flavonoid, proanthocyanidin and phytate contents of NBb (1.84 mg/g, 27.16 mg of gallic acid/g, 4.50 mg of quercetin/g, 0.98 mg of catechin/g and 8.77 mg/g dry weight of bran, respectively) were higher compared with NBr and staple varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…In the husk, a different ranking was observed, with p-coumaric acid being the dominant phenolic acid (71%), followed by ferulic acid (23%), vanillic acid (3%), and syringic acid (1%). This ranking is consistent with the values reported in most studies (Harukaze et al 1999;Tian et al 2004;Zhou et al 2004;Vichapong et al 2010;Sompong et al 2011;Tuncel and Yılmaz 2011;Chen et al 2012a;Deng et al 2012;Huang and Ng 2012;Irakli et al 2012;Jun et al 2012;Mohanlal et al 2012;Moongngarm et al 2012;Goufo et al 2014a). In KDML 105 rice, however, Butsat et al (2009) found p-hydroxybenzoic acid to be the major phenolic acid in the husk, accounting for 42% of the total phenolic acids, followed by ferulic acid (24%), and p-coumaric acid (12%).…”
Section: Phenolic Acid Composition Of Ricesupporting
confidence: 91%
See 2 more Smart Citations
“…In the husk, a different ranking was observed, with p-coumaric acid being the dominant phenolic acid (71%), followed by ferulic acid (23%), vanillic acid (3%), and syringic acid (1%). This ranking is consistent with the values reported in most studies (Harukaze et al 1999;Tian et al 2004;Zhou et al 2004;Vichapong et al 2010;Sompong et al 2011;Tuncel and Yılmaz 2011;Chen et al 2012a;Deng et al 2012;Huang and Ng 2012;Irakli et al 2012;Jun et al 2012;Mohanlal et al 2012;Moongngarm et al 2012;Goufo et al 2014a). In KDML 105 rice, however, Butsat et al (2009) found p-hydroxybenzoic acid to be the major phenolic acid in the husk, accounting for 42% of the total phenolic acids, followed by ferulic acid (24%), and p-coumaric acid (12%).…”
Section: Phenolic Acid Composition Of Ricesupporting
confidence: 91%
“…; Mohanlal et al. ), and vortexing (Huang and Ng ; Gunaratne et al. ) have also been used to obtain vitamin E isomers from rice.…”
Section: Extraction and Analysis Of Antioxidants In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid was used as reference compound and its IC50 value was 3.90 µg/ml. Similar findings were reported by Smitha (2012). c) Super oxide anion-radical scavenging activity Over-production of superoxide anion radical has long been known as the starting point of ROS/RNS accumulation in cells, contributing to redox imbalance and other associated deleterious physiological consequences (Pervaiz and Clement, 2007).…”
Section: Ml) B) Hydroxyl Radical Scavenging Activitysupporting
confidence: 72%
“…Basil is also used for pharmaceutical and cosmetic preparations due to the high content of phenolic compounds that are well-known phytochemical molecules found in all plants 7 .These constituents act as antioxidants to prevent heart disease 7 , reduce inflammation 8,9 , lower the incidence of cancers 10,11 and diabetes 12,13 , as well as reduce rates of mutagenesis in human cells (14,15) . The antioxidant activity of phenolic compounds is mainly caused by their redox properties, which permit them to act as reducing agents, hydrogen donors and singlet oxygen quenchers (16) .…”
mentioning
confidence: 99%